Efectos de uso del suelo y microclima sobre la diversidad de briófitos en vegetación riparia de bosques tropicales en el Sur del Ecuador - Vega Paccha, Marlon Rubén (2023)
Deforestation and land use by different anthropogenic activities is considered one of the main causes of biodiversity loss. Bryophytes are poikilohydric organisms and excellent quality bioindicators in the face of environmental changes. In this study we analyze how the species richness and the composition of the epiphytic bryophyte community respond to the intensity of land use and microclimatic variables in riparian vegetation of tropical forests of southern Ecuador. We selected four land use intensities (forest, forest-grassland, grassland, and urban) where 10 trees were sampled in 12 sites out of a total of 120 trees. We recorded a total of 46 bryophyte species, the species richness was highest in forest sites with 40 species, 23 for urban sites and 16 species for forest-grassland and grassland. The composition of the bryophyte communities responded to the intensity of land use and was explained by environmental variables (light) and variables classified as microclimate, for which a multidimensional nonmetric analysis (NMDS) and a multivariate analysis based on permutations (PERMANOVA). Bryophyte taxonomic diversity can be effectively applied as a bioindicator to assess and monitor the effects of land use changes on riparian vegetation in tropical regions. Keywords: Bryophytes, land use, riparian vegetation, species richness, tropical forests.